2020
DOI: 10.3389/fvets.2020.564429
|View full text |Cite
|
Sign up to set email alerts
|

Current Distribution of Selected Vector-Borne Diseases in Dogs in Spain

Abstract: Currently, climate change, modifications of landscapes and habitats due to human activities, as well as an increase in the movement of reservoirs and new species of competent vectors, have contributed to the spread of canine vector-borne diseases. These are mostly emerging and neglected diseases, some of them with zoonotic potential. Therefore, the objective of this study was to assess the prevalence and distribution of four major canine vector-borne diseases (Dirofilaria immitis, Leishmania infantum, Anaplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 69 publications
13
53
1
Order By: Relevance
“…Regarding sex, the results are similar to previous studies, which concluded that this was not a risk factor for infection. On the other hand, the significant differences found between indoor dogs when compared to indoor/outdoor and outdoor dogs were similar to other vector-borne diseases; clearly, an increased exposure to the vector increases the risk of infection [ 45 , 46 , 47 ]. The prevalence was higher in guard and hunting breed dogs; precisely, these dogs spend more hours in outdoor environments, which increases the opportunity to ingest intermediate hosts.…”
Section: Discussionmentioning
confidence: 81%
“…Regarding sex, the results are similar to previous studies, which concluded that this was not a risk factor for infection. On the other hand, the significant differences found between indoor dogs when compared to indoor/outdoor and outdoor dogs were similar to other vector-borne diseases; clearly, an increased exposure to the vector increases the risk of infection [ 45 , 46 , 47 ]. The prevalence was higher in guard and hunting breed dogs; precisely, these dogs spend more hours in outdoor environments, which increases the opportunity to ingest intermediate hosts.…”
Section: Discussionmentioning
confidence: 81%
“…Epidemiological, biological and phenological features of the Mediterranean Basin favor the presence and spreading of pathogens and parasites transmitted by vectors and/or intermediate hosts to dogs and cats [ 15 , 31 , 32 , 33 , 34 , 35 ]. Accordingly, this study confirms that dogs from regions of northern and central Italy are highly exposed to several VBDs.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmaniasis is the most relevant endemic zoonosis in the last years in the Mediterranean basin, due to the coexistence of Leishmania protozoa; reservoirs such as hare ( 11 , 40 ), rabbits ( 10 ), rodents and dogs ( 9 , 41 ), and competent vectors (sandflies from the genus Phlebotomus) . As a Mediterranean city, Barcelona has the appropriate climatic characteristics for local transmission of Leishmania sp.…”
Section: Discussionmentioning
confidence: 99%